EFEK EKSTRAK ETANOL GANGGANG HIJAU (Ulva Lactuca L) TERHADAP BERAT BADAN DAN KADAR TRIGLISERIDA TIKUS JANTAN YANG DIBERI DIET LEMAK TINGGI - Widyaningsih, Wahyu; Salamah, Nina (Universitas Ahmad Dahlan, 2015)
Previous studies showed the potential of melatonin of green algae ( Ulva lactuca L ) to reduce the risk of coronary heart disease with the activity of antihiperlipidemia. Obesity and hiperlipidemia were the risk factor of degenerative diseases such as heart disease. This research aims was explore the effect of ethanol extract of green algae against weight, consumption of rat feed test white male rat were given high fat diet . Research was started with extraction green algae with ethanol 96 % to obtained concentrated extract. The extract was tested to wistar rats age of 2 months. Animals test divided into 6 group. Group I was control group, treated with high fat diet of lard 2 ml / 200g BW, of group II given high fat diet and simvastatin, group III, IV and V given high fat diet and green algae extract doses 50 mg/ Kg BW, 100 mg/Kg BW and 200 mg/ Kg BW. Group VI is the control group without diet fat high. Treatment was conducted over 28 days. Measuring normal of his weight every five day for 28 days and in measuring consumption feed with measure weight feed the rest of feed early 20 g. The difference of data weight rats per 5 days and consumption fodder for 28 days counted area under curve ( AUC ) from curves time versus weight. The measurement of triglycerides levels. The result showed the high fat diet with lard 2 ml / 200g BW for 28 days reduce weight and consumption feed mice in a significantly than control without high fat diet. The treatment with extract ethanol dose of 50 , 100 and 200 mg / Kg BW did not reduce weight, feed consumption, triglyceride levelsofÂ mice were given high fat diet.